Microbiota Modulates Cardiac Transcriptional Responses to Intermittent Hypoxia and Hypercapnia - Zhou, Dan; Xue, Jin; Miyamoto, Yukiko; Poulsen, Orit; Eckmann, Lars; Haddad, Gabriel G. (Frontiers in Physiology, 2021)
The microbiota plays a critical role in regulating organismal health and response to environmental stresses. Intermittent hypoxia and hypercapnia, a condition that represents the main hallmark of obstructive sleep apnea in humans, is known to induce significant alterations in the gut microbiome and metabolism, and promotes the progression of atherosclerosis in mouse models. To further understand the role of the microbiome in the cardiovascular response to intermittent hypoxia and hypercapnia, we developed an efficient rodent cage system that allows exposure of mice to controlled levels of O2 and CO2 under gnotobiotic conditions. Using this experimental set up, we determined the impact of the microbiome on the transcriptional response to intermittent hypoxia and hypercapnia in the left ventricle of the mouse heart. We identified significant changes in gene expression in both conventionally reared and germ-free mice. Following intermittent hypoxia and hypercapnia exposure, we detected 192 significant changes in conventionally reared mice (96 up-regulated and 96 down-regulated) and 161 significant changes (70 up-regulated and 91 down-regulated) in germ-free mice. Only 19 of these differentially expressed transcripts (~10%) were common to conventionally reared and germ-free respectively. Such distinct transcriptional responses imply that the host microbiota plays an important role in regulating the transcriptional response to intermittent hypoxia and hypercapnia in the mouse heart.